CULTURAL, SOCIOECONOMIC, AND FAMILIAL DETERMINANTS OF CHILD PSYCHOLOGICAL DEVELOPMENT IN GHANA: A HOLISTIC PERSPECTIVE - Anobi Asare, Isaac; Dotse Komla Plahar, Joseph (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
Child psychological development is deeply influenced by a constellation of cultural, socioeconomic, and familial factors, particularly in regions with complex traditional and modern dynamics such as Ghana. This study investigates how these interrelated domains shape the mental health and behavioral outcomes of children across urban and rural settings in Ghana. Using a mixed-methods approach, we conducted surveys and semi-structured interviews with caregivers, educators, and child development professionals in Accra, Kumasi, Tamale, and selected rural communities. The findings reveal that traditional communal child-rearing practices provide a sense of security and identity, but they are increasingly strained by urbanization, economic hardship, and shifting family structures. Furthermore, socioeconomic inequality and limited access to mental health services contribute to developmental challenges, especially in underserved regions. Cultural beliefs, including stigmatization of disability and supernatural interpretations of psychological distress, further complicate early diagnosis and intervention. Despite these challenges, Ghana’s strong extended family systems and community networks remain potential assets for culturally adapted psychological support. This study emphasizes the need for contextually informed child mental health policies, inclusive education strategies, and family-centered interventions. By understanding Ghana’s unique social and cultural landscape, we can better support children’s psychological resilience and development in sub-Saharan African contexts.